Enzymatic and oxidative metabolites of lycopene (vol 14, pg 531, 2003) - Ferreira, ALD; Yeum, K. J.; Russell, R. M.; Krinsky, N. I.; Tang, G. W. (Elsevier B.V., 2004)
Using the post-mitochondrial fraction of rat intestinal mucosa, we have investigated lycopene metabolism. The incubation media was composed of NAD(+), KCl, and DTT with or without added lipoxygenase. The addition of lipoxygenase into the incubation significantly increased the production of lycopene metabolites. The enzymatic incubation products of H-2(10) lycopene were separated using high-performance liquid chromatography and analyzed by UV/Vis spectrophotometer and atmospheric pressure chemical ionization-mass spectroscopy. We have identified two types of products: cleavage products and oxidation products. The cleavage products are likely: (1) 3-keto-apo-13-lycopenone (C18H24O2 or 6,10,14-trimethyl-12-one-3,5,7,9,13-pentadecapentaen-2-one) with lambdamax = 365 nm and m/z = 272 and (2) 3,4-dehydro-5,6-dihydro-15-apo-lycopenal (C20H28O or 3,7,11,15-tetramethyl-2,4,6,8,12,14-hexadecahexaen-1-al) with lambdamax = 380 nm and m/z = 284. The oxidative metabolites are likely: (3) 2-ene-5,8-lycopenal-furanoxide (C37H50O) with lambdamax = 415 nm, 435 nm, and 470 nm, and m/z = 510; (4) lycopene-5, 6, 5', 6'-diepoxide (C40H56O2) with lambdamax = 415 nm, 440 nm, and 470 nm, and m/z = 568; (5) lycopene-5,8-furanoxide isomer (1) (C40H56O) with lambdamax = 410 nm, 440 nm, and 470 nm, and m/z = 552; (6) lycopene-5,8-epoxide isomer (II) (C40H56O) with lambdamax = 410, 440, 470 nm, and m/z = 552; and (7) 3-keto-lycopene-5',8'-furanoxide (C40H54O2) with lambdamax = 400 nm, 420 nm, and 450 nm, and m/z = 566. These results demonstrate that both central and excentric cleavage of lycopene occurs in the rat intestinal mucosa in the presence of soy lipoxygenase. (C) 2003 Elsevier Inc. All rights reserved.
Keywords: lycopene; rat; metabolites; oxidation; cleavage; enzyme